Tierra y agua en la movilización social en el Valle de Zapotitán, El Salvador (1980-2009) - Sevillano Payes, Dennis Francisco (2025)
This thesis studies how the water element developed mobilizations in the Zapotitán valley between 1980-2009. Starting from the above, this work explains the local, regional dynamics and actors that are inserted in international and national contexts since the second stage of the Green Revolution with the mechanization of agriculture that caused the construction of the first Zapotitán Irrigation and Drainage District, within the framework of national Agrarian Reform policies, which generated organizations and mobilizations that were consolidated with the neoliberal water resource privatization projects of the 1990s and early 21st century. Based on the above, the main elements to highlight in this thesis are: how the water element was not only a component for agricultural production; but also a substitute based on the tenure structure and climate change. Likewise, the favoring of the agro-industrial and industrial sectors of international projects from the Green Revolution to neoliberalism is exposed, and how the campaigns of unity and value of the popular sectors of Zapotitán transcended from the local to the national in their organization